Mechanisms Involved in the Aging-Induced Vascular Dysfunction - El Assar De La Fuente, Mariam; Angulo Frutos, Javier; Vallejo Fernán, Susana; Peiró Vallejo, Concepción; Sánchez-Ferrer, Carlos F.; Rodríguez-Mañas, Leocadio (Frontiers in Physiology, 2012)
Vascular aging is a key process determining health status of aged population. Aging is an independent cardiovascular risk factor associated to an impairment of endothelial function, which is a very early and important event leading to cardiovascular disease. Vascular aging, formerly being considered an immutable and inexorable risk factor, is now viewed as a target process for intervention in order to achieve a healthier old age. A further knowledge of the mechanisms underlying the age-related vascular dysfunction is required to design an adequate therapeutic strategy to prevent or restore this impairment of vascular functionality. Among the proposed mechanisms that contribute to age-dependent endothelial dysfunction, this review is focused on the following aspects occurring into the vascular wall: (1) the reduction of nitric oxide (NO) bioavailability, caused by diminished NO synthesis and/or by augmented NO scavenging due to oxidative stress, leading to peroxynitrite formation (ONOO-); (2) the possible sources involved in the enhancement of oxidative stress; (3) the increased activity of cyclooxygenase-derived vasoconstrictor compounds; and (4) the development of a low-grade pro-inflammatory environment. Synergisms and interactions between all these pathways are also analyzed. Finally, a brief summary of some cellular mechanisms related to endothelial cell senescence (including telomere and telomerase, as well as sirtuins) are implemented, as they are likely involved in the age-dependent endothelial dysfunction, as well as in the lower vascular repairing capacity observed in the elderly. Prevention or reversion of those mechanisms leading to endothelial dysfunction through life style modifications or pharmacological interventions could markedly improve cardiovascular health in older people.